Brand Identity Nagari Pariangan, Desa Terindah di Dunia Kabupaten Tanah Datar, Sumatera Barat - Erwin, Muhammad Syukri; Warhat, Zainal; Syafwandi, Syafwandi (Besaung : Jurnal Seni Desain dan Budaya)
A city of Pariangan is an old city in Minangkabau. A city called as the area of origin of the ancestors of the Minangkabau people that have a lot of potential both natural beauty and culture that is still exist and protected. Through the design of brand identity, the various potentials in the city of Pariangan is such a beautiful way that the creation of an effective promotional activities. So it can increase the number of tourists visiting both local and foreign. This will affect the economic sector of the community, either directly or indirectly. In the application of the concept that is inspired from the unique visual design of Pariangan city. Like the illumination motif of the ancient manuscript of Pariangan such as "Kambang Reno", a pointed roof typically of Minangkabau, roof terraced from the old mosque that became the pride of society and the typical stairs of Pariangan city. The color choice of yellow, brown and green to symbolize the natural cycles are some process of planting to harvest the rice. A brand identity of Pariangan city are designed into logos and supporting media such as stationaries, sovenir and social media that synergize together into a visual unity. The Synergy between the media will affect the image formation of the Pariangan city itself to be easier to remember and recognizeable by tourists. The successfulness of this brand identity affects the cooperation of various parties to always be consistent to apply and use this brand.